Prognosis Of Open Type 3-B Tibia Fractures by ILIZAROV Technique: A Prospective Study - Janak Rathod; Shah Taral (Medsci Publications, 2012)
Background: Open fractures of the tibial shaft are both common and may be fraught with complications. Open fractures of the tibia, with associated vascular injuries, have historically had a very poor outcome. Malunion, delayed union, nonunion, and infection are all seen regularly after open tibia fractures. Objectives: Objective of the study is to explore advantage of primary or early ilizarov surgery in Open type 3- B fracture tibia. Methodology: A follow up study of 10 cases of open type 3-B tibia fractures between 20 to 60 years of age treated with primary or early ilizarov surgery in SMIMER Hospital, Surat. Results: Among 10 patients, 9 patients showed union between 8 to 10 months. Two patients developed pin track infection which was managed with oral antibiotics and daily pin tract dressings. One patient developed disuse calf muscle atrophy and 2 patient developed equines deformity in ankle joint due to soft tissue contracture. Conclusion: Ilizarov surgery in open type 3-B tibia fracture having higher union rate with less chance of infection and obscure amputation of limb though it is technically demanding and time consuming procedure.